Optimisation of Resin Production Quantity Using De Novo Programming Models. - Eni, Yuli; Heryan, Laura Sepnivea; Rudi (Pertanika Journal of Social Sciences & Humanities)
PT. ABC is one of the well-known resin manufacturing companies that produces resin in large quantity. However, there is still residual production due to excess raw materials. The objective of this research is to find out appropriate combination of resin to be used in paint production, so that PT. ABC would achieve an optimal profit. The research method used to solve the problem is Forecasting Method and De Novo Programming. Besides, this research uses QM for Windows 2 software to support data analysis process. The results show that the demand forecast in December 2015 for each type of resin is: 240,146 kg (long type), 311,858 kg (medium type), 340,783 kg (short type), and 376.660 (other types). The combination of resin types to be produced that can optimise the production in December 2015 is: 240,146 kg (long type), 311,858 kg (medium type), 340.783 kg (short type), and 473.712,6 kg (other types). From this combination, PT. ABC would achieve optimal profit of Rp 6.388.886,315 or approximately Rp 6.3 billion.